2018
DOI: 10.1113/jp275351
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cardiac sodium channels in clusters potentiates ephaptic interactions in the intercalated disc

Abstract: It has been proposed that ephaptic interactions in intercalated discs, mediated by extracellular potentials, contribute to cardiac impulse propagation when gap junctional coupling is reduced. However, experiments demonstrating ephaptic effects on the cardiac Na current (I ) are scarce. Furthermore, Na channels form clusters around gap junction plaques, but the electrophysiological significance of these clusters has never been investigated. In patch clamp experiments with HEK cells stably expressing human Na 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 47 publications
8
99
0
Order By: Relevance
“…This is explained by the very small T-tubule diameter. At the cardiac intercalated disc, where two opposing membranes are also very close together, a similar effect has been predicted (Rhett et al, 2013;Veeraraghavan et al, 2015;Hichri et al, 2018). Importantly, sodium depletion in the T-tubule caused by sodium entering the cell may even augment the sodium current self-attenuation by decreasing the Nernst potential of sodium.…”
Section: Discussionsupporting
confidence: 53%
“…This is explained by the very small T-tubule diameter. At the cardiac intercalated disc, where two opposing membranes are also very close together, a similar effect has been predicted (Rhett et al, 2013;Veeraraghavan et al, 2015;Hichri et al, 2018). Importantly, sodium depletion in the T-tubule caused by sodium entering the cell may even augment the sodium current self-attenuation by decreasing the Nernst potential of sodium.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, Hichri and colleagues recently demonstrated that Na V 1.5 behavior is influenced by channel clustering, and localization facing narrow extracellular clefts (Hichri et al, 2018), raising the possibility of Na V 1.5 pools playing different, ultra-structure dependent roles. Here, using super-resolution STORM-RLA (Veeraraghavan and Gourdie, 2016), we further categorize ID-localized Na V 1.5 into a ‘perinexal pool’ adjacent to Cx43 and a ‘plicate pool’ that co-distributes with N-cad.…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the very small T-tubule diameter. At the cardiac intercalated disc, where two opposing membranes are also very close together, a similar effect has been predicted (Rhett et al, 2013;Veeraraghavan et al, 2015;Hichri et al, 2018). Importantly, sodium depletion in the T-tubule caused by sodium entering the cell may even augment the self-attenuation of the sodium current because this depletion will decrease the Nernst potential of sodium.…”
Section: Discussionmentioning
confidence: 54%